PREVALENCE AND PREDICTORS OF ADVERSE DRUG REACTIONS IN OLDER HYPERTENSIVE ADULTS. (April 2021) - Turrin, Giada; Coscarelli, Antonio; D'andria, Maria Flora; Tortu, Virginia; Giuliani, Evelina; Ungar, Andrea; Rivasi, Giulia
Abstract : Objective: Polipharmacy is common in older people, thus increasing the risk of adverse drufg reactrions. This study aimed to analyse prevalence and predictors of the most relevant adverse drug reactions in older hypertensive adults. Design and method: We retrospectively analysed data on antihypertensive- and statin-related adverse drug reactions in adults aged 65 or older evaluated at the Hypertension Clinic of Careggi Hospital, Florance, Italy, between January 2018 and December 2019. Predictors were investigated using multivariate logistic regression. Results: Of 262 participants (mean age 75.9 years, 55.3% female), the 19% of the patients taking ACE-inhibitors reported cough while 33.6% of the patients taking calcium channel blockers (CCB) reported peripheral edema, occuring more frequently of amlodipine. The prevalence of statin-related myalgia was 23.5%. At multivariate analysis SNRI antidepressants and gastroesophageal reflux disease (GERD) were predictive of ACE-inibitors induced cough (OR 16.220, 95% CI 1.243 – 211.621; OR 4.207, 95% CI 1.249 – 4.171, respectively) and angiotensin-receptor antagonists were associated with an increased risk of peripheral edema on CCB (OR 2.500, 95% CI 1.095 - 5.710). GERD was predictive for statin-induced myalgia (OR 6.737, 95% CI 1.530 - 29.662). Conclusions: ACE inhibitor-induced cough, CCB-related peripheral edema and statin-induced myalgia are common in older hypertensive adults. SNRI antidepressants and GERD are independently associated with ACE inhibitor-induced cough, while angiotensin-receptor antagonists are predictive of CCB-related peripheral edema. GERD is also associated with statin myalgia.